Assessment of salivary and serum antioxidant vitamins and lipid peroxidation in patients with recurrent aphthous ulceration - Saral, Y; Coskun, BK; Ozturk, P; Karatas, F; Ayar, A (Tohoku Univ Medical Press, 2005)
SARAL, Y., COSKUN, B.K., OZTURK, P., KARATAS, F. and AYAR, A. Assessment of Salivary and Sertan Antioxidant Vitamins and Lipid Peroxidation in Patients with Recurrent Aphthous Ulceration. Tohoku J. Exp. Med., 2005, 206 (4), 305-312 - Recurrent aphthous ulceration (RAU) is a common oral mucosal disorder characterized by recurrent, painful oral aphthae. Although the exact cause of RAU is not known, local trauma, microorganisms, nutritional deficiencies, hormonal changes, genetics, and immunological factors have been suggested to contribute to its pathogenesis. The aim of this study was to assess the level of lipid peroxidation and status of antioxidant vitamins in patients with RAU. Thirty patients with RAU and 20 healthy controls were recruited. Vitamins A, E, and C and malondialdehyde (NIDA) levels were measured in both serum and saliva of patients with RAU and control subjects by high performance liquid chromatography. Levels of vitamins A, E and C in both fluids were significantly lower (p < 0.05 for vitamins A and E, and p < 0.005 for vitamin C, respectively) in patients with RAU than in healthy control subjects. Conversely, the levels of MDA in serum and saliva were significantly higher (p < 0.005) in patients with RAU than in the control group. Furthermore, strong and highly significant correlation was found between serum and salivary levels of vitamins A, E and C, and MDA in patients with RAU (r >= 0.90, p < 0.0001). The present study demonstrates that the serum and saliva levels of selected antioxidant vitamins are lower, while the degree of lipid peroxidation, as judged by the MDA levels, is higher in patients with RAU than in the control subjects. This is the first to measure specific antioxidant levels in both saliva and blood in the same patients, and indicates that the non-enzymatic anti-oxidant ability is impaired in patients with RAU. - recurrent aphthous ulceration; antioxidant vitamins; MDA; nonenzymatic defense system; saliva. (c) 2005 Tohoku University Medical Press.
Keywords: recurrent aphthous ulceration; antioxidant vitamins; MDA; nonenzymatic defense system; saliva